DAKWAH MELALUI RADIO (ANALISIS PROGRAM KONSULTASI AGAMA ISLAM DI RADIO MESRA FM) - Faisal Goni; Ahmas S. Rustan; Muhammad Qadaruddin (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2016)
For media information, radio playing a significant role in conveying the values of Islam which is very important in the formation of a true Muslim personalities in accordance with the demands of the Prophet Muhammad. The existence of an Islam-based radio is felt to be very important because Islam should be spread widely and truth telling is the responsibility of the Muslims as a whole. As word of Allah in Surah al-Imran: 104.`Dari permaslahan above authors take the title essay propaganda through radio (program analysis consultancy Islam in Mesra radio FM) as the research object because the writer wanted to know how the production process of consultation Islam, what enabling and inhibiting factors Islam consultation program and analyze descriptively Islam consultation program. This research is using the case study method with the aim to explain the phenomenon through data collection techniques. This type of research is descriptive qualitative approach and used the theory of critical theory and the theory of mechanics.Hasil penelitian yang didapat adalah program konsultasi agama Islam merupakan program mingguan yang mengudara mulai pukul 10.30-11.30 disetiap hari Jum’at. The program has a dialog format or interactive manner. Factors supporting the consultation program of Islam, namely: Supported by the government and people of the city of Pare Pare while the limiting factor is the lack of public interest in consulting the religion of Islam, the lack of infrastructure in implementing the program, bad weather at the time of the program which affects not maximal broadcasting. Islam consultation program is very useful for people, especially in the town of Pare Pare, for answering complaints or problems faced by the people in the religious practice of Islam.